Aqueous crystallization of monocalcium phosphate monohydrate with green mussel shells (Verna piridis) for calcium sources. Issue 6 (December 2021) - Prihanto, A.; Fitriyana, D.F.; Muryanto, S.; Masykur, I.; Ismail, R.; Jamari, J.; Bayuseno, A.P.
Abstract: Monocalcium phosphate monohydrate (MCPM) powder with nano-size particles was synthesized by a low-cost powder precursor of green mussel shells in a laboratory magnetic stirrer. In the present study, powder processing procedures included stages of preparing the raw mussel shells into the high-quality precipitated calcium carbonate (PCC) through washing, size reducing, ball milling, intensive calcination, and carbonation in the nitric acid solution. Moreover, the MCPM powder was synthesized by reacting PCC powder with the phosphoric acid in aqueous-water media at the 90 °C with four stirring time durations (30, 60, 90, and 120 min). Additionally, analytical methods such as X-ray powder diffraction (XRD), FTIR spectroscopy, and scanning electron microscopy (SEM/EDX) were applied for examining the raw- and synthesized powders. The resulting PCC product contained vaterite (91.26 wt%), and calcite (8.74 wt%). The use of PCC polymorph for the synthesis provided the high purity of MCPM nanoparticles in stirring time durations (from 30 to 90 min). However, the increased stirring time duration of 120 min yielded the second phase of monocalcium phosphate anhydrous (MCPA). Instead, more homogenous particle size was further obtained with increasing stirring time. This reproducible and low-cost approach would be a promising strategy for recycling green mussel shells into large-scale MCPM products. Graphical Abstract: ga1 Highlights: The experimental approach of converting green mussel shells into value-added ceramics. Powder processing of shells yielded for the synthetic biomaterials of calcium phosphates. Green mussel shells have an important component of bio-minerals. High grade monocalcium phosphate monohydrate with homogenous nanoparticles.